Intrathoracic desmoid tumor arising at a distance from thoracotomy sites after thoracoscopic segmentectomy: report of a case - Endo, Tetsuya; Endo, Shunsuke; Yamamoto, Shinichi; Tetsuka, Kenji (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
We report a case involving an intrathoracic desmoid tumor in a 68-year-old woman who had undergone video-assisted thoracoscopic right basal segmentectomy for lung cancer 1 year earlier. The well demarcated tumor was 9 cm × 6 cm × 6 cm in size, was located in the right apico-posterior thorax and had invaded the chest wall. The patient complained of a dull shoulder pain as a result of rapid tumor enlargement. En bloc tumor resection, including the apico-posterior chest wall extending from the 1st to the 4th rib, was successful. The patient had no recurrent tumor at 5 years after the second surgery. Intrathoracic desmoid tumor could occur, even when the tumor arises at a distance from the port and thoracotomy sites after thoracoscopic surgery.